Pengabdian kepada Masyarakat melalui Pembuatan Produk Minuman Timun Apel sebagai Upaya Meningkatkan Ekonomi dan Ketahanan Pangan Lokal - Ekalia Yusiana; Slamet Abadi; Suroso Suroso; Siti Maryani (Institut Pertanian Bogor, 2024)
Apple cucumber is an annual plant that belongs to the Cucurbitaceae family and is very closely related to the melon plant. Regarding morphology and fruit aroma, this plant is a hybrid plant or a cross between melon and suri cucumber. Apple cucumber farmers in Tanjungpakis Village cultivate an average of ½Ha land for apple cucumber cultivation. The taste of the apple cucumber produced by the fruit is sweet, and the flesh is soft, making this fruit much liked by the public. This makes apple cucumber a superior local fruit that is cultivated in Tanjung Pakis Village. The aim of implementing community service is to make apple cucumbers a strategic superior commodity to be processed into beverage products, optimize the potential of local and regional products, and help improve the economy and welfare of farmers in rural areas. The implementation method is carried out through outreach and licensing, training and practice, and assistance to farmers. The results obtained from the service implementation are syrup product innovations that have been packaged and equipped with attractive product labels.